Casting e-sports: a vivência das mulheres nos esportes eletrônicos - Costa, Cláudia Piazza Rodrigues Tavares (2021)
Electronic sports emerge gradually stronger in the 21st century as a sport genre. It combines the feeling of competitiveness, traditional in any sporting dispute, with with the new and increasingly sophisticated technologies and the games that were created, initially, as a form of entertainment. Moving billions of dollars annually and drawing the attention of big companies. e-Sports have become a phenomenon, with structured competitions and millionaire prizes to their competitors. Like all social relationships, the competitive landscape of electronic games is dominated by men, with few women managing to establish themselves professionally among them, either as players or narrators and commentators. Thus, the present work sought to understand what experiences were lived by women who became professional in the casting of electronic sports, using interviews to identify similarities and differences in these experiences. It was possible to notice that the two interviewees had family support while establishing their career and institutional support in the moments when they faced gender violence